Hysteresis Phenomena and Their Modelling in Martensitic Transformation Thermodynamics - Likhachev, O.A.; Koval, Yu.M. (Успехи физики металлов, 2015)
In the present review paper, we show that a successful description of the irreversible evolution of macroscopic variables during the martensitic transformations caused by hysteresis is possible with using a special type of differential equations with the temperature-dependent coefficient depending only on the main hysteresis loop shape. These equations make it possible to predict the macroscopic volume fraction evolution for an arbitrary temperature change process including the partial subloops. For this aim, one should know only the information about the temperature behaviour for transformation paths representing the main hysteresis loop. The present model is practically applied and experimentally confirmed for martensitic transformation in CuZnAl alloy. В данной обзорной статье показано, что успешное описание необратимой эволюции макроскопических переменных, обусловленной гистерезисом в процессе мартенситных превращений, возможно путём использования дифференциальных уравнений специального типа с температурнозависимыми коэффициентами, которые определяются исключительно формой основной петли гистерезиса. Эти уравнения дают возможность предсказывать эволюцию макроскопической фракции мартенсита для произвольного процесса изменения температуры, включая частичные петли мартенситного превращения. Для этого необходимо знать лишь её поведение на основной петле гистерезиса. Указанная модель практически применена и экспериментально проверена для случая мартенситного превращения в сплаве CuZnAl. У даній оглядовій статті показано, що успішний опис незворотньої еволюції макроскопічних змінних, зумовленої гістерези в процесі мартенситних перетворень, є можливим при використанні диференційних рівнянь спеціяльного типу з температурозалежними коефіцієнтами, що визначаються виключно формою основної петлі гістерези. Ці рівняння дають можливість передбачати еволюцію макроскопічної частки мартенситу для довільного процесу зміни температури, включаючи часткові петлі мартенситного перетворення. Для цього потрібно знати лише її температурну залежність для основної петлі гістерези. Зазначений модель практично застосовано та експериментально перевірено для випадку мартенситного перетворення у стопі CuZnAl.